Bemerkungen zu einem speziellen Kegelkarstvorkommen in Nord-Thailand - Ludwig, Manfred (ERDKUNDE, 1976)
Out of the utmost northern part of Thailand special cone karst phenomena are reported. The genesis of these forms is a result of close connections between tectonic and corrosive processes. Therefore the author suggests the name “Karstkamme (karst ridges).